Investigation of the Solubility of the Ternary Systemkcl – K2SO4- H2O - Z. T. Ruzieva; M. F. Dustmurodova (International Journal on Orange Technologies, 2022)
The possibility of practical use of a substance is entirely determined by its properties. When addressing this issue, the economic feasibility of its application is also considered. Therefore, before finding a use for a substance, its physical and chemical properties are first studied in detail. After that, the boundaries of the use of the substance become clear.